Investigating the impact of partner inclusion on behavior : a field study in workplace HIV prevention programming - Petrozzola, Helen (Stellenbosch : Stellenbosch University, 2009)
Thesis (MPhil (Industrial Psychology))--Stellenbosch University, 2008.